Peran Pondok Pesantren Al-Zaytun Dalam Meningkatkan Ekonomi Masyarakat Sekitar - Prawoto, Imam; Anisa, Fitri (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
Educational institutions in Indonesia consist of various types, one of which is Islamic boarding schools. Islamic boarding schools are the oldest Islamic educational institutions in Indonesia. The majority of Muslims in Indonesia have established many Islamic boarding schools in this country. The current role of Islamic boarding schools is not only as educational institutions, but also as institutions that can increase economic value through programs contained in Islamic boarding schools. The purpose of this study was to find out and analyze the role of the Ma'had Al-Zaytun Islamic boarding school in improving the economy of the surrounding community. This research was conducted at al-Zaytun Islamic Boarding School. This research is a descriptive qualitative research. Data sources were obtained from interviews, observations, and literature studies related to the research topic. The results of this study found that in addition to being an Islamic educational institution, the Al-Zaytun Islamic boarding school also has considerable resources, so that with these resources the Al-Zaytun Islamic boarding school can carry out various activities, one of which has economic centers both in agriculture, animal husbandry, fishery and cooperatives that can help improve the economy of the Al-Zaytun community and the surrounding community, such as providing loans and capital from the Ma'had Al-Zaytun Islamic boarding school cooperative; P3KPI provides land and capital for those who want to farm with a profit sharing system from the harvests obtained; Providing employment for the surrounding community, especially to manage Ma'had Al-Zaytun's agriculture and plantations; and distribution of harakah zakat and harakah Qurban to the community around the Islamic boarding school.